Perhitungan Risiko Nilai Tukar atas Posisi Devisa Netto Bank X Melalui Pendekatan Value At Risk (VaR) - Susanto, Tri (Business and Management Review, 2010)
This study was conducted at the Bank X Jakarta, while the samples from this study are on the Net Open Position. The model used in this study is a descriptive study of quantitative models. The study was conducted to measure the risks that may arise from changes in exchange rates based on net open position of 31 December 2007 and calculate Capital Charge based on Net Open Position as of December 31, 2007. Effective risk management requires measurement attempts to determine the amount of capital that must be prepared to cover the risk and be used for strategic planning activities of foreign exchange by the Bank. Selection of study topics is based on the need for measurement methods that banks will be able to measure the potential risk in a comprehensive manner that is able to measure the sensitivity of the potential risk of product or activity of factors - factors that influence it. The maximum loss on risks resulting from changes in exchange rates are calculated through the approach of Value at Risk (VaR) using Historical Simulation method for each foreign currency and in the form of portfolio under the provisions of the Bank for International Settlements (BIS) as outlined in the provisions of Basel II, which then adopted by Bank Indonesia in PBI. 5/8/PBI/2003 dated May 19, 2003 and the rules of Bank Indonesia Regulation. 9/13/PBI/2007 about the use of internal methods for measuring market risk. The result of exchange rate risk measurement approach to Value at Risk (VaR) with Historical Simulation method ruing a time horizon of 1 day and performed at the 99% confidence level, the losses that may be suffered by Bank X Jakarta on January 1, 2007 is at a maximum of Rp. 507 322 635 762. And based on the calculation of the percentage of capital charge against capital is known that at 116.92% of the total capital charge compared with the total capital. This amount is still above the limit set by Bank Indonesia, which are as high as 30% of the capital.   Keywords: capital charge, exchange rates, value at risk, historical simulation method, foreign currency